Reinventing Islamic Education Management: When Islamic Humanism Meets the Future of Policy, Technology, and Human Flourishing - Hamdanah Hamdanah (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This study explores the integration of Islamic Humanism into the management of contemporary Islamic educational institutions, examining how leadership, curriculum, technology, and community engagement collectively contribute to holistic human development. Employing a qualitative research design, data were collected through semi-structured interviews, focus group discussions, document analysis, and non-participant observations across multiple pesantrens and madrasahs. Findings indicate that humanistic leadership fosters ethical decision-making, participatory governance, and policy frameworks prioritising the dignity and flourishing of students, teachers, and communities. The integration of technology and interdisciplinary curricula enables students to engage with classical knowledge while developing critical thinking, ethical reasoning, and practical skills relevant to modern society. Additionally, community engagement initiatives operationalise ethical principles, promoting empathy, civic responsibility, and socially oriented action. Together, these interconnected dimensions demonstrate that Islamic education guided by humanistic principles can balance tradition and modernity, preparing learners to navigate contemporary challenges, contribute positively to society, and achieve holistic intellectual, moral, and social development. The study provides a comprehensive model for Islamic educational management that aligns spiritual and ethical objectives with the demands of twenty-first-century learning.